MULTICULTURAL PARADIGM AND DA'WAH STRATEGY BUILDING RELIGIOUS MODERATION IN REJANG LEBONG - Dede Mercy Rolando; Hariya Toni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The research looks at how the multicultural paradigm influences one's experience and what is the da'wah strategy in dealing with a multicultural society? To conduct this research, the researcher uses a mixed method research (qualitative and quantitative) which aims to combine two methods at once in order to obtain more comprehensive, valid, reliable and objective data. The subjects and objects of this research are students from 3 high schools in Rejang Lebong, Curup city, namely SMAN 1, SMAN 2 and SMAN Xaverius. The results of the research show that the portrait of the paradigm of experience High school students in Rejang Lebong have high enough confidence to consistently interact and adapt to differences. In fact, it is not only considered a luxury, but is interpreted as a necessity where they cannot avoid religious differences. This has implications for their multicultural behavior where they are able to be smart in responding to differences. In this context, the experience of students' multicultural behavior has a very good level of religious and cultural moderation. Of course, this is based on the cultivation of a formal and non-formal understanding of multiculturalism. This study found several strategies that were obtained in order to be able to carry out religious and cultural moderation in a multicultural society including: planting an understanding of the value of tolerance through an educational approach (crosscultural education) to develop universal values that can be accepted by different groups of people, cultural approaches and language, as well as approaches through socio-religious psychology.